2017
DOI: 10.1080/19322909.2017.1356257
|View full text |Cite
|
Sign up to set email alerts
|

User Navigation in Large-Scale Distributed Digital Libraries: The Case of the Digital Public Library of America

Abstract: This article presents the findings of a case study that examined user navigation in a large-scale digital library in the context of academic use. Using the Digital Public Library of America as case, the study explored user navigation and understanding of a distributed model of large-scale digital libraries. The DPLA model involves two-or three-step navigation pathways. Most study participants could navigate the DPLA distributed, multi-layered system effectively. This study found some confusion among the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…First, it is important to note the multiplicity of the DPLA's audiences (Matusiak, 2017) and to recognize that these have not always been clearly distinguished in planning and strategy…”
Section: Who Are the Digital Public?mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is important to note the multiplicity of the DPLA's audiences (Matusiak, 2017) and to recognize that these have not always been clearly distinguished in planning and strategy…”
Section: Who Are the Digital Public?mentioning
confidence: 99%
“…First, it is important to note the multiplicity of the DPLA's audiences (Matusiak, 2017) and to recognize that these have not always been clearly distinguished in planning and strategy documents. An emphasis on "access" and empowering "the public," which has been reiterated in the DPLA's strategic plans, contributes to this vagueness.…”
Section: Who Are the Digital Public?mentioning
confidence: 99%
“…In another study, focusing on millennial populations in Pakistan, Soroya and Ameen (2018) found that the users are more comfortable with using the DL if it could be easily accessed 24/7. In the USA, Matusiak (2017) discovered that a good system navigation will help the users of the Digital Public Library of America to locate and access wider digital resources easily. In Portugal, Pinho et al (2019) discovered that deep knowledge on the use of digital resources helps to improve the ease of use, which will increase DL acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers have documented the difficulties experienced by users in navigating the portals of the Digital Public Library of America and Europeana, where users encounter a record for the item, as opposed to the item itself, and must navigate links from the portal out to the collections containing the digital objects. 40 Specifically, some participants in Matusiak's study were confused when they reached DPLA service hubs, struggling with a path that linked them from the DPLA site to the service hub to the object from their search results. These studies suggest that instruction also should include 41 basic knowledge about the structure of digital library systems, so that students know what to expect and how to successfully navigate to their search results.…”
Section: Finding and Evaluating Digital Primary Sourcesmentioning
confidence: 99%